STUDENTS’ ERRORS IN PROBLEM-SOLVING REVIEWED FROM THE PERSPECTIVE OF MATH RESILIENCE - Utami, Wikan Budi; Dewi, Aulia Puspita; Widodo, Sri Adi (Universitas Pelita Harapan, 2024)
The purpose of this research is to: 1) identify students' mistakes in solving mathematical problems in trigonometry in terms of mathematical resilience according to the Newman Procedure, and 2) discuss trigonometric problems from the point of view of mathematical resilience according to the Newman Procedure. This type of research is qualitative. The research subjects were 3 students from SMA Negeri 1 Slawi, selected using a purposive sampling technique. The methods of data collection are tests, questionnaires, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the data analysis, we obtained the following: (1) Students' mistakes in reading the questions include: students do not understand the context of the sentence, students do not correctly understand the meaning, and students do not read all the meanings of the desired words. (2) The answers to the questions include: answers that do not contradict the accepted answers but do not coincide with the inquiry accepted in the question, and answers that do not address what is required in the problem posed, often being a question of application. (3) Transforming the problem includes: considering a method being investigated, using the wrong method, and not translating the method to be used. (4) Process skills contain: concept errors, errors in computing, not continuing the settlement procedure, and not processing calculations. (5) The final answer includes: an answer that fits the context of the question, and an answer that does not match the conclusion. The contributing factors include: lack of self-confidence, confusion in describing the problem in the form of a picture, hurrying in solving problems, lack of accuracy, inability to manage time well, inability to think about problems thoroughly, forgetting to identify what is suitable and trying, confusion in determining the formula to be used, and solving the problem without completing the conclusion.